Quicksilver - Koontz, Dean R. (Dean Ray), 1945- (Thomas & Mercer, 2022)
When the discovery of a coin worth a lot of money forces him to run for his life, Quinn Quicksilver meets his destined companions as he barrels towards a confrontation with an enemy who is as every bit as scary as the power within himself.